2014
DOI: 10.1038/srep03655
|View full text |Cite
|
Sign up to set email alerts
|

Systemic risk and spatiotemporal dynamics of the US housing market

Abstract: Housing markets play a crucial role in economies and the collapse of a real-estate bubble usually destabilizes the financial system and causes economic recessions. We investigate the systemic risk and spatiotemporal dynamics of the US housing market (1975–2011) at the state level based on the Random Matrix Theory (RMT). We identify richer economic information in the largest eigenvalues deviating from RMT predictions for the housing market than for stock markets and find that the component signs of the eigenvec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 38 publications
4
75
0
Order By: Relevance
“…Recently, the largest eigenvalue has been successfully used as a predicting index for sudden changes in complex systems, such as the financial crisis 21,53 and the housing market. 22 Previous studies have suggested that characterizing the largest eigenvalue of an adjacency matrix of complex networks is useful for better understanding the network behavior. In our experiment, the largest eigenvalue provided the most information about the contribution of different brain regions to the dynamic brain network.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the largest eigenvalue has been successfully used as a predicting index for sudden changes in complex systems, such as the financial crisis 21,53 and the housing market. 22 Previous studies have suggested that characterizing the largest eigenvalue of an adjacency matrix of complex networks is useful for better understanding the network behavior. In our experiment, the largest eigenvalue provided the most information about the contribution of different brain regions to the dynamic brain network.…”
Section: Discussionmentioning
confidence: 99%
“…25 The RMT was proposed initially to measure the spectral fluctuation and has found widespread applications in different real systems. [21][22][23][24][25][26][27][28][29][30][31][32][33] Therefore, we used the RMT method to further explore the dynamic brain network. NNSD is the distribution of spacing between eigenvalues and only accounts for the relationship between neighboring eigenvalues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Varsha Kulkarni analyzed the volatility of the Indian stock market based on stochastic matrix theory [5]. Based on the knowledge of stochastic matrix, Meng and Xie used absorption rate, linear regression and clustering methods to study the correlation degree and division of the American real estate market, and found that the risk of the American estate market was very high and the whole market was unstable [6,7]. Tian, et al investigated the information and characteristics of the international crude oil market (1999-2015) based on the random matrix theory [8].…”
Section: Literature Review Of Stochastic Matricesmentioning
confidence: 99%
“…In order to further study the influence of the eigenvalues of the correlation coefficient matrices C(t) on the natural gas import market in OECD countries, we define R n (t ) = u T n (t )r(t ) (6) where, t = t − L + 1, · · · , t, r(t ) = [r 1 (t ), r 2 (t ), · · · , r 7 (t )] T . We construct a regression model…”
Section: Feature Combination Algorithmmentioning
confidence: 99%